Tilik Kaji Tradition in Wonosobo: Between Prayer, Solidarity, and Social Ethics - Puji Laksono (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2026)
This research aims to examine the social, religious, and cultural significance in the tradition of tilik kaji (visiting prospective pilgrims) in the rural Muslim community of Wonosobo. This tradition is carried out before the departure of the Hajj. The research uses a qualitative approach with ethnographic methods. Data collection is through observation, in-depth interviews, and documentation of prospective pilgrims, families, community leaders, and residents involved in the tradition. Data analysis was carried out thematically to understand the relationship between cultural practices, religious values, and social relations of the community.The results of the research are that the tradition of the hajj ritual not only functions as a practice of friendship, but also as a medium for strengthening social solidarity, mutual cooperation culture, and the reproduction of people's religious values. The practice of bringing consumer necessities reflects the collective participation of the community in helping the host. In addition, the choice to visit before departure shows the social ethics of the community that avoids the impression of asking for souvenirs after returning from the hajj. This study recommends the importance of preserving local religious traditions as part of strengthening the social cohesion of rural Muslim communities.